Migraine headache and risk of self‐harm and suicide: A population‐based study in Ontario, Canada. Issue 1 (31st October 2015) - Colman, Ian; Kingsbury, Mila; Sareen, Jitender; Bolton, James; van Walraven, Carl
Abstract : Background: Migraine has been associated with mental illness, and may also be associated with increased risk of suicidal behavior. Objective: The aim of this article was to examine the association between migraine headache and self‐harm and suicide mortality using population‐based health administrative data from Ontario, Canada. Methods: The sample included 101, 114 participants in a population‐based health survey in the province of Ontario, Canada, who responded to the survey in 2003, 2005, or 2007, and provided health card numbers for linkage to population‐based health administrative data. Participants self‐reported a physician diagnosis of migraine headache. Heath administrative data were used to calculate (1) Follow‐up time until first presentation to the emergency department for intentional self‐harm; (2) Follow‐up time until death by suicide. Proportional subdistribution hazards regression was used to compare time until death among those with and without history of migraine, after accounting for competing risks of death and adjusting for confounders. Results: Physician diagnosis of migraine was reported by 11.2% of the sample (11, 314 individuals). Mean follow‐up time was 7.3 years. Emergency department visits for self‐harm during the follow‐up period were almost 50% more likely in those with migraine (76.4 vs 35.7 per 100, 000 person years; adjusted hazard ratio = 1.48; 95%CI: 1.11, 1.96). Death by suicide was rare with only 55 suicides in the follow‐up period (7.45 per 100, 000 person‐years). Risk of suicide was similar for both those with and without history of migraine headache (adjusted hazard ratio=0.60; 95%CI: 0.22, 1.65). Conclusions: Physician diagnosis of migraine headache was found to be prospectively associated with increased risk of deliberate self‐harm, but there was no evidence linking it to suicide mortality. Definitively linking migraine to death by suicide may require very large samples. Health care professionals should consider monitoring suicidal risk in individuals with migraine headache.